In the land of giants: the legacy of José Dantas de Souza Leite - Hélio A. G. Teive; Plínio M. Lima; Francisco M.B. Germiniani; César L. Boguszewski (Arquivos de Neuro-Psiquiatria)
The authors describe the extraordinary contribution to science made by José Dantas de Souza Leite, who graduated from the Bahia School of Medicine and trained in Prof. Charcot’s Neurology Service under the supervision of Charcot’s most able pupil, Dr. Pierre Marie. Souza Leite presented his doctoral thesis on acromegaly, in Paris in 1890, and in the following year both him and Pierre Marie published a book on the subject, “Essays on Acromegaly”. This exceptional work established Souza Leite internationally as an important researcher, and the first Brazilian physician to contribute to the development of neuroendocrinology in an innovative way.